Postoperative liver gas gangrene - Perdomo, Roberto; Pereyra Borrelli, César; Gravina, Francisco (Cirugía del Uruguay, 2020)
Two cases of postoperatory hepatic gaseous gangrene are studied. An analysis is made of the ch,racteristics which are useful for a better interpretation of pathological facts: bacterian flora in the normal liver; sources, migration paths of anaerobian germs; conditions which favour infection and are dependent on the surgical aggression. In the diagnostical aspect, we notice the need to be acquainted with this disease as a possible cause of septic shock in the postoperatory period, immediately following hepatic or hepatobilliary surgery. The main therapeutical measures for safeguarding the lives of this patients are ennumerated.